MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS MELALUI MODUL KELARUTAN DAN HASIL KELARUTAN BERBASIS DISCOVERY LEARNING WITH TEKNIK PROBING PROMPTING DI SMAN 1 PARIAMAN - Fefri Perrianty; Tri Haryanti (MIDWIFERY HEALTH JOURNAL, 2019)
Abstract: This study aims to determine the improvement of student critical thinking based on discovery learning with probing prompting techniques the material of ion equilibrium in salt solution (salt hydrolysis). The research design used was the Design of the Posstest Non-Equivalent Group. The population in this study was students of class XI IPA SMAN 1 Payakumbuh 2018/2019 academic year. The selection of sample classes is done by cluster purposive sampling technique. The sample in this study was class XI IPA 3 as the control class and XI IPA 4 as the experimental class. The learning experimental class uses modules discovery learning with probing prompting techniques, while the control class without using modules. The research instrument used was a test of the results of learning critical thinking questions. The results showed that modules discovery learning with probing prompting techniques can improve students' critical thinking skills, as evidenced by the increase in the average in the posttest results. The results of testing for normality and homogeneity state that the critical thinking value of the two distributed samples is normal and homogeneous. Hypothesis test results obtained by GIS. (2-tailed) of 0.002 <0.05 means that the value of critical thinking learners who use modules is based on discovery learning with probing prompting techniques significantly different.